2022
DOI: 10.3390/educsci12110789
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effects of Specific Types of Self-Efficacy on the Relationship between Math Anxiety and Performance

Abstract: The negative relationship between math anxiety and math performance is well-supported in the literature. The important role of students’ math self-efficacy (i.e., their confidence in their ability to successfully complete specific math tasks) in this relationship is also established. Self-efficacy is extremely specific, however, and it is possible that additional types of self-efficacy can play a role in the relationship between anxiety and performance. This study surveyed 118 undergraduate students on their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…Social relationships and connectedness are also important dispositional characteristics influential to adults’ learning. McLean's (2015), Jameson's (2022), and Sagna and Vaccaro's (2023) work all found that adult learners regularly report motivation to engage in learning to either benefit or support their relationships with others.…”
Section: Dispositions Toward Learning In Adult Learnersmentioning
confidence: 99%
See 2 more Smart Citations
“…Social relationships and connectedness are also important dispositional characteristics influential to adults’ learning. McLean's (2015), Jameson's (2022), and Sagna and Vaccaro's (2023) work all found that adult learners regularly report motivation to engage in learning to either benefit or support their relationships with others.…”
Section: Dispositions Toward Learning In Adult Learnersmentioning
confidence: 99%
“…Math anxiety can begin as early as preschool for some students but becomes more common in elementary school and can continue through middle‐, high‐, and post‐secondary schools and professional settings (Barroso et al., 2021). A strong negative relationship exists between math anxiety and math performance (Foley et al., 2017), due to some combination of decreased cognitive resources (Ashcraft & Moore, 2009) and math anxiety's inverse relationship with math self‐efficacy (Jameson et al., 2022; Palestro & Jameson, 2020; Skaalvik et al., 2015). Jameson and Fusco's (2014) work comparing adult learners and traditional undergraduate students showed an increase in math anxiety as students' age increased; Stacey (2023), however, did not find a difference in math anxiety levels between traditional and adult learners.…”
Section: Dispositions Toward Learning Mathematicsmentioning
confidence: 99%
See 1 more Smart Citation